(untitled) (Bangladesh Heart Journal, 2017)
Aims: To compare the risk factors and pattern of coronary artery involvement in young acute coronary syndrome patients with that of the elderly. Methods: This was a cross sectional analytic study done in the Department of Cardiology, Sir Salimullah Medical College and Mitford Hospital during November 2015 to October 2016. Results: Study population was divided into two subgroups, those 18-40 years were considered as young and those >40 years were considered as elderly. Young patients had greater prevalence of smoking, dyslipidemia and positive family history of Ischemic Heart Disease (IHD), whereas hypertension was more prevalent in the elderly. Younger patients mainly presented with STEMI and predominantly had single vessel disease (SVD), whereas elderly patients frequently presented with NSTEMI and Unstable angina and had higher incidence of double vessel disease (DVD) and triple vessel disease (TVD). Conclusion: Younger patients had a different pattern of risk factors and coronary artery involvement in comparision to the elderly. Bangladesh Heart Journal 2017; 32(1) : 40-44